Lost Worlds, Lost Paradises: Primitive City and Impossible Utopia in "Those Who Are Not Descended from Eve" (1941), by Luis Antonio de Vega - Martín Rodríguez, Mariano (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2013)
The crisis of Modernity in mid-twentieth century led to a paradigm shift in lost world fiction. Unlike former imperialist fantasies in which the lost race was symbolically incorporated into the allegedly superior Western civilization, several modernist lost world romances depict primitive societies endowed with utopian perfection, embodying thus the accomplished dream of paradise. Unfortunately, contemporary mankind does not always seem worthy of enjoying the primitive desired city. For example, in the lost race tale Those Who Are Not Descended from Eve (1941), by Luis Antonio de Vega, man is inherently flawed and unable to return to the lost paradise. This brilliant Spanish example of lost world fiction skilfully exploits the pessimistic notion of an essentially impossible utopia.